2010
DOI: 10.1093/jnci/djq239
|View full text |Cite
|
Sign up to set email alerts
|

Breast Tissue Composition and Susceptibility to Breast Cancer

Abstract: Breast density, as assessed by mammography, reflects breast tissue composition. Breast epithelium and stroma attenuate x-rays more than fat and thus appear light on mammograms while fat appears dark. In this review, we provide an overview of selected areas of current knowledge about the relationship between breast density and susceptibility to breast cancer. We review the evidence that breast density is a risk factor for breast cancer, the histological and other risk factors that are associated with variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
353
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 394 publications
(367 citation statements)
references
References 130 publications
10
353
0
4
Order By: Relevance
“…The associations between salivary and serum estradiol (SD) and progesterone (SD) and percent mammographic density (%), stratified by tertiles of HDL-C HDL-C <1.39 increased low-grade inflammation (44), and higher levels of total endogenous estradiol and estradiol locally produced in the breast (44,45). Moreover, immune cells and cytokines may interact in a paracrine manner with ovarian steroids in mammary cells (48), and support the present observation, and the hypothesis that mediators of inflammatory cellular cascades, such as low HDL-C, may influence mammographic density phenotypes (12).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The associations between salivary and serum estradiol (SD) and progesterone (SD) and percent mammographic density (%), stratified by tertiles of HDL-C HDL-C <1.39 increased low-grade inflammation (44), and higher levels of total endogenous estradiol and estradiol locally produced in the breast (44,45). Moreover, immune cells and cytokines may interact in a paracrine manner with ovarian steroids in mammary cells (48), and support the present observation, and the hypothesis that mediators of inflammatory cellular cascades, such as low HDL-C, may influence mammographic density phenotypes (12).…”
Section: Discussionsupporting
confidence: 84%
“…Mammographic density refers to the structure and relationship of the adipose, epithelial, and stromal tissues (12,13). Percent mammographic density reflects relative amounts of fibroglandular and fat tissue, and absolute mammographic density reflects epithelial and stromal tissues, the dense areas of the breast (14,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, it is still contentious whether density is an independent risk factor or merely stimulates other risk factors to cause cancer. Regardless of these contentions, studies have shown that high breast density is associated with a 4-6 fold increased risk of breast cancer, [2][3][4][5] and that a 1% increase in breast density is associated with 2% increase in breast cancer risk. 4 Dense breast tissue has been shown to offer more opportunities for breast cancer to develop, especially in younger women.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of these contentions, studies have shown that high breast density is associated with a 4-6 fold increased risk of breast cancer, [2][3][4][5] and that a 1% increase in breast density is associated with 2% increase in breast cancer risk. 4 Dense breast tissue has been shown to offer more opportunities for breast cancer to develop, especially in younger women. 3,[6][7][8] Additionally, there is a genetic predisposition to breast density, 9,10 and other established risk factors for breast cancer such as hormonal agents, 11,12 lifestyle, and reproductive characteristics are associated with high breast density.…”
Section: Introductionmentioning
confidence: 99%